2017
DOI: 10.1007/s41887-017-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

The “Power Curve” of Victim Harm: Targeting the Distribution of Crime Harm Index Values Across All Victims and Repeat Victims over 1 Year

Abstract: Research Question Is the vast majority of crime harm in one police force area over 1 year suffered by a small percent of all known victims, with many of those mostharmed victims suffering repeated and perhaps preventable crimes if more police resources were to be invested in them? Data All 30,244 crimes recorded as committed against all 25,831 persons with one or more known victimization reported between 1 June 2015 and 31 May 2016 in Dorset, UK. Methods Each criminal event was weighted by the Cambridge Crime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Similarly, we will ask authors of research on the concentration of harm among victims to use the more neutral terminology of 'high-priority victims' to describe the most harmed (as in Dudfield et al 2017). As for studies on targeting high-harm or highcrime volume locations, we see no reason to avoid using 'harm spots' or 'hot spots' as the terminology, or even a 'power few' subset of hot spots where most crime or harm is concentrated.…”
Section: Naming the Few: High-harm Places Victims And Offendersmentioning
confidence: 99%
“…Similarly, we will ask authors of research on the concentration of harm among victims to use the more neutral terminology of 'high-priority victims' to describe the most harmed (as in Dudfield et al 2017). As for studies on targeting high-harm or highcrime volume locations, we see no reason to avoid using 'harm spots' or 'hot spots' as the terminology, or even a 'power few' subset of hot spots where most crime or harm is concentrated.…”
Section: Naming the Few: High-harm Places Victims And Offendersmentioning
confidence: 99%
“…It has also led to the identification of such concentrations in other dimensions of crime, in which a small number of units account for a large proportion of total crime event volume (Sherman 2007). For example a small proportion of all locations experience most crimes (Sherman et al 1989), a small proportion of victims suffer the majority of crime harm (Farrell 1995;Dudfield et al 2017) and a small proportion of all offenders have the most criminal convictions (Farrington et al 2013).…”
Section: Tracking Offenders Over Timementioning
confidence: 99%
“…In domestic violence studies, a very small subset of offenders has been found to cause the most harm to victims (Barnham, Barnes, & Sherman, 2017;Bland and Ariel 2015). Dudfield et al (2017) have shown that fewer than 5% of victims suffer 85% of the harm, with sex offences and robbery contributing almost two-thirds of total harm (63%). Similarly, a small subset of organised crime groups (OCGs) and gangs produce the most harm where these groups operate .…”
Section: The 'Power Few' Of the Targeting Of The Most Harmful Offendersmentioning
confidence: 99%
“…Numerous evidencebased targeting strategies have emerged in recent years, establishing one clear and consistent theme: not all crimes or criminals are equally harmful (Sherman et al 2016). The evidence points to a clear "Pareto curve" phenomenon: not only are most criminal events attributable to a small group of people, places or times (Sherman 2007); so, too, is most crime harm concentrated in a small percentage of places (Weinborn et al 2017), victims (Dudfield et al 2017) and victim-offenders (Sandall et al 2018).…”
Section: Introductionmentioning
confidence: 99%